2021
DOI: 10.1111/ene.14745
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease patients' needs during the COVID‐19 pandemic in a red zone: A framework analysis of open‐ended survey questions

Abstract: Background and purpose During the first phase of the COVID‐19 pandemic, a lockdown was imposed in Italy. The aim of this study was to investigate the perceptions, feelings and unmet needs of Parkinson's disease (PD) patients who experienced the 2‐month lockdown in a “red zone” in the northern part of Italy during the COVID‐19 outbreak. Methods The study had a descriptive design that used a cross‐sectional online survey which included open‐ended questions to elicit respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…Twelve studies questioned whether their physical activity and/or sports Questionnaires (IPAQ) and Physical Activity Scale for Individuals with Physical Disabilities (PASIPD) results assessed before and after the lockdown (Marco-Ahulló et al, 2021 ; Shalash et al, 2020 ) Three studies included healthy controls Brown et al, 2020 ; di Stefano et al, 2020 ; Shalash et al, 2020 ), but two of them compared physical activity levels of healthy controls and people with neurological diseases (di Stefano et al, 2020 ; Shalash et al, 2020 ). Two studies also included caregivers (Borges-Machado et al, 2020 ; Cavallieri et al, 2021 ) Answers were obtained from caregivers of dementia patients, whereas in the study that included persons with Parkinson’s disease, the caregivers were asked when patients could not respond (Borges-Machado et al, 2020 ; Cavallieri et al, 2021 ). Brown et al included participants with and without COVID-19 and presented subgroup analysis for the baseline characteristics, but they provided data for information on physical activity or exercise of participants without COVID-19 (Brown et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies questioned whether their physical activity and/or sports Questionnaires (IPAQ) and Physical Activity Scale for Individuals with Physical Disabilities (PASIPD) results assessed before and after the lockdown (Marco-Ahulló et al, 2021 ; Shalash et al, 2020 ) Three studies included healthy controls Brown et al, 2020 ; di Stefano et al, 2020 ; Shalash et al, 2020 ), but two of them compared physical activity levels of healthy controls and people with neurological diseases (di Stefano et al, 2020 ; Shalash et al, 2020 ). Two studies also included caregivers (Borges-Machado et al, 2020 ; Cavallieri et al, 2021 ) Answers were obtained from caregivers of dementia patients, whereas in the study that included persons with Parkinson’s disease, the caregivers were asked when patients could not respond (Borges-Machado et al, 2020 ; Cavallieri et al, 2021 ). Brown et al included participants with and without COVID-19 and presented subgroup analysis for the baseline characteristics, but they provided data for information on physical activity or exercise of participants without COVID-19 (Brown et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used the IPAQ to assess physical activity levels 6,22,25 . In the 11 studies, a constructed survey was used to determine whether physical activity/sport activities/exercise has changed during the pandemic (Borges-Machado et al, 2020 ; Brown et al, 2020 ; Cavallieri et al, 2021 ; Kalron et al, 2021 ; Kumar et al, 2021 ; Prada et al, 2020 ; Sanchez-Larsen et al, 2020 ; Schirinzi et al, 2020 ; Song et al, 2020 ; van de Venis et al, 2020 ; van der Heide et al, 2020 ); (Schirinzi et al, 2020 ). used both IPAQ and structured surveys.…”
Section: Resultsmentioning
confidence: 99%
“…A report from Italy evaluated the needs of patients with PD during the COVID-19 pandemic [39]. Among others, patients reported a reduction of physical activity, perception of the risk of not being able to access outpatient clinics or support services, and negative experiences of the reduction in socialization.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 103 PD patients reported four main problems in the first Italian lockdown: 1. fear of contracting corona, 2. reduction of physical activity, 3. not being able to access support services and clinics and 4. reduction of socialization [ 148 ]. There was an objective reduction of physical activity, measured by a smartphone application, as most PD patients failed to meet 30 min of activity per day [ 149 ].…”
Section: Chaptermentioning
confidence: 99%